Enzymatic vitreolysis with recombinant tissue plasminogen activator for vitreomacular traction - Raczyńska D; Lipowski P; Zorena K; Skorek A; Glasner P (Drug Design, Development and Therapy, 2015)
Dorota Raczyńska,1 Paweł Lipowski,1 Katarzyna Zorena,2 Andrzej Skorek,3 Paulina Glasner1 1Department of Ophthalmology, Medical University of Gdańsk, Poland; 2Department of Immunobiology and Environment Microbiology, Medical University of Gdańsk, Poland; 3Department of Otolaryngology, Medical University of Gdańsk, Poland Aims: The aim of our research was to gain data about the efficacy of intravitreal injections of a recombinant tissue plasminogen activator (rTPA) in dissolving vitreoretinal tractions (VRTs).Materials and methods: The study group consisted of patients of our Ophthalmology Clinic who had received an injection of rTPA (TPA Group) for an existent vitreomacular traction confirmed by optical coherence tomography and stereoscopic examinations. The control group consisted of patients who had declined treatment despite the existence of a vitreomacular traction confirmed by the same diagnostic methods. Each group consisted of 30 people (30 eyes). The observation period was 6 months.Conclusion: In both groups some of the VRTs had dissolved. In the TPA group the traction dissolved in 10 patients (33.33%) and in the control group only in 5 (16.67%). It is also important to point out that the mean baseline membrane thickness was higher in the TPA group than in the control group. Observing patients in both groups we noticed that the dissolution of vitreoretinal membrane occurred most frequently in those cases where the membrane was thin. In the TPA group, the mean membrane thickness after 6 months decreased considerably. At the same time, no significant change in the membrane thickness could be observed in the control group. Observation of the retinal thickness allows us to draw the following conclusion: in the TPA group, the retinal thickness in the macular area (edema) had decreased over the study period, whereas in the control group it had increased. In those cases where the traction had dissolved, the edema of the retina decreased by the end of the 6-month period in both groups. In the TPA group, the dissolution of the membrane occurred most often within 3 months from the primary injection. Based on statistics, we can confirm that in the control group there was a decrease in visual acuity during the 6 months of the study period. At the same time, visual acuity in the TPA group underwent a small improvement. A 6-month observation had shown that in patients with strong VRTs, and in particular with VRTs accompanied by epiretinal membranes, a single intraocular injection is not enough to achieve posterior vitreous detachment. We have also shown that rTPA is a safe drug, with no adverse effects observed during the study period. Keywords: tissue plasminogen activator (rTPA), vitreous body, macular hole, vitrectomy, epiretinal membrane, diabetic retinopathy